Meningkatkan Kemampuan Siswa dalam Keterampilan Menulis Menggunakan Board Game di Kelas 10 SMK BNKP Daro-Daro Balaekha Lahusa - Hasrat Sozanolo Harefa; Ichsan Telaumbanua (INTELEKTIUM, 2022)
Writing is  a transaction with words whereby someone free his self from what he presently think, feel and perceive. In learning writing, most of the students could not achieve the MCC. There were some problems faced by the students in studying writing descriptive text at the tenth grade of SMK Swasta BNKP Daro-daro Balaekha Lahusa in 2020/2021 namely: the students were lack of vocabularies. The students were unable to describe the object. The students were unable to identify topic, main idea, content from descriptive text. Therefore, to overcome the problems, the researcher conducted a research by using Board Game at the Tenth Grade of SMK Swasta BNKP Daro-daro Balaekha Lahusa in 2020/2021. The purpose of the research is to increase the students’ ability in writing descriptive text. In increasing the students’ writing descriptive text, the researcher used Board Game and applied as Classroom Action Research (CAR). The  research has been conducted in two cycles, which each cycle consisted of two meetings, there were four steps in conducting the research namely (1) Planning, (2) Action, (3) Observation (4) Reflection. The result of the data in Cycle I that the average score was 44.64, the maximum score was 7.14 and the minimum score was 50. While in Cycle II the average score was 82.14; the maximum score was 72 and the minimum score was 28. From the result of the research, It can be concluded that Board Game Increase the Students’ Ability Writing Descriptive Text at the Tenth Grade of SMK Swasta BNKP Daro-daro Balaekha Lahusa in 2020/2021.